Difusi Inovasi Kesehatan Masyarakat Melalui Program Jamban Arum (Antar Ke Rumah) di Kecamatan Simpangkatis Kabupaten Bangka Tengah - Debi Devia; Siti Aisyah (JIAPI: Jurnal Ilmu Administrasi Dan Pemerintahan Indonesia, 2020)
This study described the diffusion of public health innovation through the Arum Latrine Program (delivery to houses) in Simpangkatis District, Central Bangka Regency, which was carried out as an effort to improve performance through community services and development, especially in the community health development. The Arum Latrine Program was a program implemented from, by and for the Simpangkatis District with funding sourced from voluntary self-subsistent, so that currently the Arum Latrine Program was being proposed as one of the regional innovations. The research method used a qualitative approach with descriptive methods. Data collection was conducted through interviews and observations. The interview was conducted to the informants who were selected using purposive sampling technique (the head of Simpangkatis District and sub-district employees, the head of village and village office staff, the Sector Police Chief, and the head of Simpangkatis health center) and snowball sampling technique (the community leaders and community recipients of Arum Latrine Program in the Simpangkatis District area). The data were analyzed using the theory of Everett M. Rogers (1964). The conclusions were: 1) The diffusion innovations of public health through the Arum Latrine Program (Delivery to Houses) in Simpangkatis District had not been going well and had not been widely adopted. 2) The most powerful aspect in the diffusion of Arum Latrine innovation was the social system. 3) The obstacles in the diffusion of Arum Latrine innovation were the culture of open defecation among the community, the lack of initiative from other agencies to adopt the Arum Latrine Program, and misunderstandings of the apparatus in accepting the socialization of the Arum Latrine Program, especially regarding to the collection of voluntary donations. 4) The factor that supported the program was the social system existing in the community. It was because ??Simpangkatis District was still thick with its customs and culture, so that this social system became the most effective communication network in the diffusion of Arum Latrine innovation.